التغيرات الصوتية في الأفعال الثلاثية: دراسة حاسوبية نظرية تطبيقية - المهيوبي، عبدالعزيز بن عبدالله (جامعة الأميرة نورة بنت عبد الرحمن, 2018)
ترمي الدراسة إلى بيان أهم التغيرات الصوتية التي تطرأ على بنية الكلمة في اللغة العربية ممثلة في بنية الفعل الثلاثي المجرد عند إسناده إلى ضمائر الرفع، وهي محاولة لتجاوز وصف القدماء لتلك التغيرات الصوتية إلى توصيف يؤهلها للترميز، ومن ثمة حوسبتها. واعتمد الباحث على طريقة اختزل بها الأفعال الثلاثية المجردة؛ باستبدال رموز رقمية محددة بعناصر الأفعال الأصلية. وتكمن أهمية الدراسة في كونها تسلط الضوء على التغيرات الصوتية التي تطرأ على أفعال اللغة العربية عند تصريفها، وهي ظاهرة من أكثر الظواهر الصرفية إشكالا عند حوسبتها. وتطمح الدراسة إلى تقديم نموذج يصلح أن يكون أساسا لمعالجة التغيرات الصوتية في كلمات اللغة العربية، وتراكيبها. كما يسعى الباحث إلى وضع أساس علمي، يمكن للباحثين اللغويين والحاسوبيين الارتكاز عليه لبناء مشروع متكامل لحوسبة تصريف أفعال اللغة العربية الثلاثية والرباعية، وتوليدها. The study aims to explain the most important vocal changes that occur to the structure of the word in the Arabic language represented in the structure of the root verb when attached to a nominative pronoun. And it is an attempt to overcome the description of the vocal changes given by the scholars of the past towards a description that better qualifies it for coding purposes, which can then be computerised. The Researcher relied on a method to minimise the root verbs; by substituting numeric symbols for the elements of the original verbs. The importance of this study lies in the fact that it sheds light on the occurring vocal changes on the Arabic verbs when conjugated, and this is one of the most complicated morphological phenomena during the computing stage. This study aims to put forth a model that can serve as the basis for addressing the vocal changes in the Arabic words and its conjugates. The researcher also seeks to establish a scientific basis which can then be used by linguists and computer experts to build an integrated project for the computerisation and generation of the Arabic verbs.
Keywords: تكنولوجيا المعلومات -- التغيرات الصوتية -- الأفعال الثلاثية -- الدراسات الحاسوبية -- الفنون الموسيقية